The book of blood and shadow - Wasserman, Robin (2012)
While working on a project translating letters from sixteenth-century Prague, high school senior Nora Kane discovers her best friend murdered with her boyfriend the apparent killer and is caught up in a dangerous web of secret societies and shadowy conspirators, all searching for a mysterious ancient device purported to allow direct communication with God
Keywords: Paranormal fiction; Secret societies -- Juvenile fiction; Conspiracies -- Juvenile fiction; Murder -- Juvenile fiction; Prague (Czech Republic) -- Juvenile fiction; Czech Republic -- Fiction; Mystery fiction